Phenotype of a patient with contiguous deletion of TBX5 and TBX3: Expanding the disease spectrum. Issue 5 (24th March 2014) - Bogarapu, Soujanya; Bleyl, Steven B.; Calhoun, Amy; Viskochil, David; Saarel, Elizabeth V.; Everitt, Melanie D.; Frank, Deborah U.
<x xml:space="preserve">Abstract</x> The important roles that T‐box genes play in the morphogenesis of the heart and its conduction system has long been established, and a number of disorders are linked to mutations in these T‐box genes. Holt–Oram syndrome (HOS), the classic heart and hand syndrome, is clinically typified by radial ray upper limb abnormalities and cardiac malformations, and is caused by mutations involving TBX5. Another member of the T‐box gene family, TBX3, is found in close proximity to TBX5 on chromosome 12q24. Mutations in TBX3 cause ulnar–mammary syndrome (UMS), which is distinguished by upper limb malformations affecting the ulnar ray, apocrine, and mammary gland hypoplasia, and genital defects. While disorders involving isolated mutations of TBX5 and TBX3 have been well described, contiguous deletions of these T‐box genes remain exceptional. We report on a patient with features of both HOS and UMS consisting of bilateral symmetric limb malformations, congenital cardiac defects, and rapidly progressive cardiac conduction disease. © 2014 Wiley Periodicals, Inc.